Prywatne przyjmowanie I wspieranie osób uciekających przed wojną w Ukrainie: Raport badawczy - Marta Cwalina; Paweł Downarowicz; Anna Firgolska; Marta Gospodarczyk; Maria Jonik; Brunon Roch Kuryło; Anna Pruszyńska; Anna Skiba; Anna Wydra (University of Warsaw, Centre of Migration Research (CMR), 2023)
– The report's objective is to present the results of a qualitative research dedicated to private admission and support of war refugees from Ukraine, who have crossed into Poland after 24th February 2022. The report presents findings from the first phase of the research, that is the analysis of thirty individual interviews with persons actively and consistently helping the refugees in Masovian voivodeship. The research focused on the motivations of those helping refugees, their needs, and challenges they have met. After discussing the theoretical frames which constitute the point of reference for our analysis, namely community sponsorship and homestay support, we provide an overview of quantitative research on help offered Ukrainian refugees, which was conducted at the same time as the qualitative part of the study, which provides an important context for the rest of the report. Then, we present the methodology of the research, which proceeds the presentation of the results in the following areas: the motivations of the individuals helping the refugees, strategies of communication between those helping and the refugees they help, the stages of creating closeness and personal relationships between the refugees and their helpers, the challenges met by the participants, and the benefits from helping. The report ends with an attempt to summarise similarities and differences between community sponsorship programs and the support offered to war refugees in Poland.
Keywords: 330; war refugees from Ukraine; community sponsorship; private support of refugees